Gasification of Miscanthus x giganteus Pellets in a Fixed Bed Pilot-Scale Unit - Samson, Abby; Mos, Michal; Najser, Jan; Daroch, Maurycy; Gallagher, Joe (Frontiers in Energy Research, 2018)
Gasification of Miscanthus x giganteus (Mxgig), is highly promising due to the high efficiency of the process and the many advantageous properties of this crop. Pilot-scale, fixed bed gasification studies were performed utilizing this fuel at three temperatures (750, 850, 950 ºC) to determine the process effects of temperature on gas quality and tar yields. Simple thermodynamic equilibrium modeling was successfully applied to the pilot-scale gasification process. The Mxgig crop performed well, with best process stability reached at temperatures of 800 ºC or higher. Average calorific values of the product gases were highest at around 850 ºC at 5.2 MJ.m-3. Tar yields gradually increased with increasing temperature and dropped after 900 ºC. The presented thermodynamic equilibrium model conformed well with experimental results, deviating little in terms of O2, CO2, H2 and CH4 and no more than 8.1% in the case of CO. This indicates that simple modeling methods can be utilized to predict gas compositions for the pilot-scale.